2014
DOI: 10.3390/nu6104610
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on the Hypoglycemic and Antioxidative Effects of Fermented Paste (Doenjang) Prepared from Soybean and Brown Rice Mixed with Rice Bran or Red Ginseng Marc in Mice Fed with High Fat Diet

Abstract: Abstract:The effects of fermented paste made from soybean, brown rice, or brown rice in combination with rice bran or red ginseng marc on the glucose metabolism and antioxidative defense system in high fat-fed mice were investigated. The mice were given experimental diets for eight weeks: Normal control, high fat, and high fat supplemented with soybean fermented paste, brown rice fermented paste, brown rice-rice bran fermented paste, or brown rice-red ginseng marc fermented paste. The high fat group showed mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 46 publications
6
29
0
Order By: Relevance
“…Similar to the case of preparing CH 2 OO, adduct formation (R3) is also expected and would reduce the yield of CH 3 CHOO at high pressures. 22,23 Removing the contribution of anti-CH 3 CHOO Fig. 1 20 we may separate their signals by tting the time traces with two exponential functions (eqn (1)).…”
Section: Resultsmentioning
confidence: 99%
“…Similar to the case of preparing CH 2 OO, adduct formation (R3) is also expected and would reduce the yield of CH 3 CHOO at high pressures. 22,23 Removing the contribution of anti-CH 3 CHOO Fig. 1 20 we may separate their signals by tting the time traces with two exponential functions (eqn (1)).…”
Section: Resultsmentioning
confidence: 99%
“…This process allows the improvement of food functionality as free forms of phenolic compounds are inclined to represent higher bioactivities than the corresponding polysaccharide-bound forms (Subba Rao & Muralikrishna, 2002). Increasing evidence of in vitro and in vivo researches has suggested that the fermented WBR products have multiple preventive and therapeutic effects against carcinogenesis, oxidative stress, inflammation and glucose homeostasis disorders (Chung, Rico, & Kang, 2014;Kuno et al, 2015;Onuma et al, 2015). Despite a promising tool to produce WBR-based products with desirable organoleptic, nutritional and functional attributes, fermentation process involves in obvious transformation in the form of food matrix and in most cases, the WBR flour rather than integral grains is used as the fermenting substrate for optimum metabolic activity of the inoculated microbes, which may limit the application of fermentation in WBR processing.…”
Section: Fermentationmentioning
confidence: 99%
“…The demand for the addition of red ginseng to a variety of food products and the use of various feed additives has recently increased (Chung et al, 2014). Red ginseng marc is a water-insoluble byproduct remaining after the red ginseng extraction process.…”
Section: Growth Performance and Fatty Acid Profiles Of Broilers Givenmentioning
confidence: 99%